STRENGTHS AND WEAKNESSES TO FACE THE DYING AND DEATH PROCESS: STUDENTS' REFLECTIONS - Sandoval, Sylvia Álvarez; Vargas, Mara Ambrosina de Oliveira; Zilli, Francielly (My University, 2020)
ABSTRACT Objective: to identify the strengths and weaknesses recognized by the students to face the dying process and death in the hospital setting. Method: a qualitative and descriptive approach. The sample was made up of 19 students of the fifth-year of the Nursing course, complying with the in-hospital professional practice, and the study was carried out at a university in the Magallanes and Chilean Antarctic Region, Chile, between September and October 2018. The collected data were submitted to the precepts of Content Analysis. Results: among the identified strengths, the following are to be mentioned: previous experience with death, the support provided by the guiding nurse during hospital stay, the student's mental maturity, soft skills, and sensitivity. In its turn, the limitations identified include lack of experience, psychological immaturity, the few tools they possess, factors associated with the patient such as age, and the affective bonds created with the patient that may end up causing suffering to the student. Conclusion: both the strengths and weaknesses recognized by the students must be worked on in the academy throughout the training, in such a way that the students may acquire the necessary tools to face the process of death and dying. Death must be discussed as an integral phenomenon in order to achieve a better understanding of this topic by the students, so that they can act in the best possible way in front of terminal patients, providing quality and humanized care for the patients and/or families.
Keywords: death; nursing education; hospital care; bioethics; attitude facing death